2016
DOI: 10.1073/pnas.1601571113
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping Beautyscreen revealsPpargactivation in metastatic prostate cancer

Abstract: Prostate cancer (CaP) is the most common adult male cancer in the developed world. The paucity of biomarkers to predict prostate tumor biology makes it important to identify key pathways that confer poor prognosis and guide potential targeted therapy. Using a murine forward mutagenesis screen in a Pten-null background, we identified peroxisome proliferator-activated receptor gamma (Pparg), encoding a ligand-activated transcription factor, as a promoter of metastatic CaP through activation of lipid signaling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
101
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 41 publications
4
101
1
Order By: Relevance
“…Numerous studies have shown that FSAN, the catalyst of the final step in fatty acid synthesis, is overexpressed and strongly related with tumor malignant progression [2126]. HAO Q et al demonstrated that genetic inhibition of FASN expression suppressed the invasion and migration of HCC cells, indicating the contribution of FASN to malignant HCC tumor metastasis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that FSAN, the catalyst of the final step in fatty acid synthesis, is overexpressed and strongly related with tumor malignant progression [2126]. HAO Q et al demonstrated that genetic inhibition of FASN expression suppressed the invasion and migration of HCC cells, indicating the contribution of FASN to malignant HCC tumor metastasis [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is well accepted that adenocarcinomas of the prostate utilize lipids to fuel their growth, and dysregulated lipid metabolism is observed in PCa . Recent work has demonstrated that the nuclear receptor peroxisome proliferator‐activated receptor γ (PPARγ), which regulates the expression of proangiogenic genes, is overexpressed in metastatic prostate adenocarcinomas and is associated with reduced patient survival …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Recent work has demonstrated that the nuclear receptor peroxisome proliferator-activated receptor γ (PPARγ), which regulates the expression of proangiogenic genes, is overexpressed in metastatic prostate adenocarcinomas and is associated with reduced patient survival. [5][6][7] Fatty acid-binding protein 5 (FABP5) is a member of a class of intracellular lipid chaperones that transports fatty acids to PPARγ, leading to increased expression of proangiogenic factors including vascular endothelial growth factor, which can result in a metastatic phenotype. 5,[8][9][10][11][12] The normal prostate lacks FABP5 expression but it becomes highly upregulated in PCa and the degree of its upregulation correlates with increasing Gleason scores, indicating that advanced metastatic prostate tumors express the highest levels of FABP5.…”
mentioning
confidence: 99%
“…Of these, YAP1, a Hippo pathway target promoting tumor growth 64 , can also be regulated by non-canonical WNT signaling, and can in turn inhibit canonical WNT signaling 50 . PPARG a regulator of lipid metabolism is involved in various cancers, although the evidence is mixed about its role in driving cancer metastasis 65 . LPIN1, a negative regulator of PPARG activity, can therefore also be linked to Wnt signaling through this regulatory molecule.…”
Section: Discussionmentioning
confidence: 99%